A MAC protocol for Underwater Sensors Networks - Santos, Rodrigo Martin (2015)
Underwater sensor networks are becoming an important field of re- search, because of its everyday increasing application scope. Examples of their application areas are environmental and pollution monitoring (mainly oil spills), oceanographic data collection, support for submarine geo-localization, ocean sampling and early tsunamis alert. It is well-known the challenge that represents to perform underwater communications provided that radio signals are useless in this medium and a wired solution is too expensive. Therefore, the sensors in these network transmit their information using acoustic signals that propagate well under water. This data transmission type bring an opportunity, but also several challenges to the implementation of these networks, e.g., in terms of energy consumption, data transmission and signal interference. Few proposals are avail- able to deal with the problem in this particular application scenario, and these proposals does not address properly the transmission of underwater acoustic signals. In order to help advance the knowledge in the design and implementation of these networks, this paper proposes a MAC protocol for acoustic communications between the nodes based on a self-organized time division multiple access mechanism. The proposal is still preliminary and it has only been evaluated in the laboratory; however, it represents a highly promising behavior that make us expect interesting results in real-world scenarios.